Natural convection heat transfer test for in-vessel retention at prototypic Rayleigh numbers – Results of COPRA experiments. (January 2016) - Zhang, Y.P.; Zhang, L.T.; Zhou, Y.K.; Tian, W.X.; Qiu, S.Z.; Su, G.H.; Zhao, B.; Yuan, Y.D.; Ma, R.B.
Abstract: Large-scale COPRA experiments were performed to investigate the natural convection heat transfer in melt pools for the in-vessel retention during severe accidents in Chinese large-scale advanced PWRs. Both water and binary mixture of 20 mol% NaNO3 – 80 mol% KNO3 were used as the melt simulant material in performed tests. Due to the full scale geometry of the COPRA test section, the Rayleigh numbers of the melt pool could reach up to the prototypic magnitude of 10 16 . Natural convection heat transfer tests at prototypic Rayleigh numbers have been performed to study the influence of the heat generation rate and melt simulant material on the melt pool temperature, heat flux distribution and heat transfer capability. The comparisons of the melt pool temperature and heat flux distribution from water experiments and molten binary salt experiments showed that the crust formation along the inner surface of the vessel wall could impact the heat transfer characteristics of the melt pool. And the heat flux distribution from COPRA water tests and molten salt tests were in good agreement with those from Jahn-Reineke water experiments and RASPLAV molten salt experiments, respectively. The heat transfer capability of the melt pool Nu dn from COPRA molten salt tests were larger than those from water tests, but both were lower than those from ACOPO and BALI predictions within the same range of Rayleigh numbers (10 15 – 10 17 ). Highlights: Investigating melt pool behavior in the RPV lower head experimentally. Comparison of heat transfer characteristics with different simulants. Obtaining heat transfer correlation of melt pool.